2010
DOI: 10.4269/ajtmh.2010.09-0663
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity, Pathogenicity, and Virulence of Trypanosoma cruzi Isolates from Sylvatic Animals and Vectors, and Domestic Dogs from the United States in ICR Strain Mice and SD Strain Rats

Abstract: Abstract. Trypanosoma cruzi , the causative agent of Chagas disease, is widespread in the southern United States. In addition to detection in numerous wildlife host species, cases have been diagnosed in domestic dogs and humans. In the current investigation, groups of laboratory mice [Crl:CD1 (ICR)] were inoculated with one of 18 United States T. cruzi isolates obtained from a wide host range to elucidate their infectivity, pathogenicity, and virulence. In addition, laboratory rats (SD strain) were inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
2
15
1
2
Order By: Relevance
“…cruzi DTUs caused differential infection dynamics in mice and rats as determined by PCR detection of T . cruzi DNA in the blood and tissues [57]. These authors found that sylvatic TcI isolates from the United States had greater infectivity to laboratory rodents than TcIV isolates, contradicting our results with isolates from Brazilian Amazon.…”
Section: Discussioncontrasting
confidence: 99%
“…cruzi DTUs caused differential infection dynamics in mice and rats as determined by PCR detection of T . cruzi DNA in the blood and tissues [57]. These authors found that sylvatic TcI isolates from the United States had greater infectivity to laboratory rodents than TcIV isolates, contradicting our results with isolates from Brazilian Amazon.…”
Section: Discussioncontrasting
confidence: 99%
“…If this features is reproduced in human hosts, an important implication is the lack or delay in diagnosis of acute Chagas disease, since direct methods are being used and recommended in the Amazon region because this is the same approach used for the detection of malaria cases, which would make a parallel program control. These data support the findings of previous studies, which reported that sylvatic stocks from the United States, where the TcI and zymodeme 3 genotypes circulate, as in the Brazilian Amazon, were largely avirulent and did not cause morbidity or mortality in rodent models 25 . In contrast, T. cruzi stocks from the classic endemic areas of South America readily infect a wide variety of laboratory mouse strains and many cause significant morbidity and mortality 12,16,26 .…”
Section: Ethical Considerationssupporting
confidence: 82%
“…In our study, the majority of genetic variability was noted in the TcIV isolates. Interestingly, TcIV isolates from the US tend to be less virulent to laboratory mice and to date, no human infections with this genotype have been reported in North America [49]; TcIV strains have been isolated from primates, prosimians, and domestic dogs [34], [50], [51]. Previously, different T. cruzi MSH2 phenotypes have exhibited different levels of susceptibility to cisplatin and oxidative damage [48], [52].…”
Section: Discussionmentioning
confidence: 99%